(untitled) (2015)
As a part of its development plans and educational Project, Universidad de Medellín, Colombia, intends to focus its research efforts on information and communications technology –ICT–. There is still a lack of information about the strengths that need to be enhanced, which makes focalization of capabilities a difficult task. The University needs to create a niche in which it would be recognized and distinguished from other institutions. To achieve this aim, a strategy in order to guide the ICT research activities within the University is proposed. This article reflects on a number of research trends to be taken into account as organizational directives that allow an optimal use of resources and infrastructure. For this purpose a qualitative perspective and a hermeneutic methodological approach are used. Former research findings reveal that Universidad de Medellín should research on topics related to education, technology infrastructure, policy and regulatory environment, software development, digital content, management and administration of organizations. In order to show a clearer view, every topic is divided into subgroups. With this mapping of the trends it would be possible for the University to optimize its efforts on IT research and to be recognized for its achievements in that field. This initiative should be completed by an effective communication strategy that informs the community on all the levels of the topics. © 2015, Universidad de Tarapaca. All rights reserved.